SYNERGISTIC EFFECT OF DIFFERENT CONCENTRATIONS OF SODIUM CHLORIDE AND SODIUM TRIPOLYPHOSPHATE ON PHYSICOCHEMICAL PROPERTIES AND SENSORY ATTRIBUTES OF MARINATED BROILER BREAST FILLETS - S. Ali1; S. Nazir; M. Hayat; K. Nauman; J. Nasir; M. Sohaib; M. A. Khan (Journal of Animal and Plant Sciences, 2020)
The objective of this study was to evaluate the comparative effect of combination of different concentrations of salts on quality, yield and sensory attributes of broiler breast meat. Breast fillets were vacuum tumbled for 20 minutes with 20% (based on meat weight) marinade solution. Marinade solution was made using different concentrations of sodium chloride (NaCl) and sodium tripolyphosphate (STPP). A total of 84 breast fillets were used in this trial, and the fillets were divided into 7 groups. The 1st group (no marination) was kept as control group (T○), 2nd group was treated with 3% NaCl (T1) solution in water (w/w), 3rd group was treated with 1.5% NaCl and 0.3% STPP (T2). Similarly 4th , 5th , 6th , and 7th groups were treated with 1.25% NaCl + 0.35% STPP (T3), 1% NaCl + 0.4% STPP (T4), 0.75% NaCl + 0.45% STPP (T5), 0.5% NaCl + 0.5% STPP (T6) ,respectively. The pH, color, marinade pick up and loss, cooking yield, tenderness, water holding capacity and sensory attributes were evaluated. By treating with T5 shear force values (tenderness) were improved significantly (P ≤ 0.05) when compared with other marination treatments and the control group. In addition, the breast fillets that were treated with T3 and T4 showed significantly (P ≤ 0.05) higher cooking yields and highly acceptable to the sensory panel than other treatments. Therefore, it was concluded that relatively low concentration (0.75-1.25%) of sodium chloride in combination with low concentration (0.35-0.45%) of sodium tripolyphosphate could improve the quality and sensory attributes of fresh vacuum tumbled poultry meat.
Keywords: sodium chloride; sodium tripolyphosphate; vacuum tumbling; broiler breast meat